1992
DOI: 10.1164/ajrccm/146.1.263
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-5 Modulates Eosinophil Accumulation in Allergic Guinea Pig Lung

Abstract: Based on its involvement in eosinophil biology, interleukin 5 (IL-5) may play a role in the pulmonary eosinophilia associated with allergic reactions. We have examined that hypothesis using a neutralizing antibody to IL-5 in ovalbumin-sensitized guinea pigs challenged with aerosolized antigen. The extent of eosinophilia has been quantitated in bronchoalveolar lavage (BAL) and by histologic evaluation of lung tissue sections. Acute intraperitoneal administration of a rat IgG, monoclonal antibody to murine IL-5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
69
1

Year Published

1995
1995
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(76 citation statements)
references
References 11 publications
6
69
1
Order By: Relevance
“…It is possible that increased serum level of IL-5 may originate from several tissues, including lungs, local lymph nodes, and bone marrow. However, the exact site of action of anti-IL-5 on allergen-induced airway eosinophilia has not been clearly described in several previous studies in which anti-IL-5 was administered systemically (27)(28)(29)(30)(31)(32). A recent study has shown that the anti-IL-5 Ab delivered via the airway route attenuates allergen-induced eosinophilia in BAL and lung tissues (47).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that increased serum level of IL-5 may originate from several tissues, including lungs, local lymph nodes, and bone marrow. However, the exact site of action of anti-IL-5 on allergen-induced airway eosinophilia has not been clearly described in several previous studies in which anti-IL-5 was administered systemically (27)(28)(29)(30)(31)(32). A recent study has shown that the anti-IL-5 Ab delivered via the airway route attenuates allergen-induced eosinophilia in BAL and lung tissues (47).…”
Section: Discussionmentioning
confidence: 99%
“…The first class, in this study termed type I, is exemplified by chicken egg OVA which, aside from airway hyperresponsiveness (1), is incapable of inducing a broad spectrum of lung allergic changes which additionally include goblet cell metaplasia, mucus oversecretion, airway eosinophilia, and peribronchovascular inflammation, if given strictly by inhalation. However, OVA is capable of inducing all of these allergic changes if given remote from the lung in a series of priming doses, typically with aluminum-based adjuvants before intrapulmonary challenge (2)(3)(4)(5)(6)(7)(8)(9)(10)(11). In contrast, the other major class of allergen, in this study termed type II, is derived from the fungus Aspergillus fumigatus and readily induces allergic lung inflammation when given only through the airway and without the need for additional adjuvant (12)(13)(14).…”
Section: Efining the Immunopathologic Basis Of Allergic Inflam-mentioning
confidence: 99%
“…IL-5 administration has been shown to increases mucosal exudation, enhance eosinophil recruitment into the lungs and to increases airways responsiveness in models of allergen induced BHR in the guinea pig (Gulbenkian et al 1992, van Oosterhout et al 1993a, in mice (van Oosterhout et al 1993b), and in the Brown Norway rat (Renzi et al 1996). Moreover, anti-IL-5 administration inhibits eosinophil recruitment and airways hyperresponsiveness in guinea pig models of allergic pulmonary inflammation and allergen induced BHR (Gulbenkian et al 1992, van Oosterhout et al 1993a, Das et al 1995. Similar findings have also been demonstrated in the the mouse (Nagai et al 1993 and in the monkey .…”
Section: Il-5 and Anti-il-5 Administrationmentioning
confidence: 99%